Acetaldehyde accumulation during wine micro oxygenation: The influence of microbial metabolism. (December 2022) - Dai, Lingmin; Zhong, Ke; Cui, Xiaoqian; Ma, Yan; Hou, Zhaohua; Sun, Yuhang; Han, Guomin
Abstract: Acetaldehyde is a key oxidation product during red wine micro oxygenation (Mox) and it appears to accumulate by the metabolism of residual yeast Saccharomyces cerevisiae ( S. cerevisiae ), which may be difficult to detect by plating due to low numbers. The aim of this study was to investigate the roles and interaction of S. cerevisiae and lactic acid bacterial (LAB) with regard to acetaldehyde accumulation during red wine Mox treatment. Immediately after alcohol fermentation using three different yeast S. cerevisiae strains, some wine was sterile filtered, and of that, some was inoculated with the same three yeasts. All were treated with Mox; acetaldehyde and malolactic fermentation (MLF) were monitored. Besides, the capacity of LAB to metabolize acetaldehyde was also evaluated in model wine. The results showed that Mox appeared to maintain S. cerevisiae populations, and the survival of S. cerevisiae postponed spontaneous MLF. S. cerevisiae did produce acetaldehyde during Mox, while levels varied by strains, production rates declined during treatment, and levels dropped after treatment ended. The appearance of LAB coincided with an increase in production, but levels later dropped more quickly when LAB were present. Residual sugar and amino acid levels did not change significantly during microbial metabolism of Mox wines. The acetaldehyde generated from chemical oxidation continued to accumulate during Mox. In the experiment of model wine, LAB was shown to produce acetaldehyde in the inception phase and a certain amount of acetaldehyde did not influence the start of MLF. The results confirmed the variation character of acetaldehyde with microbial action and can serve as a theoretical underpinning for better control of Mox applications in enology. Highlights: Acetaldehyde accumulation from microbes and chemical oxidation are different. Reinforced survival of yeast postpones but can't eradicate spontaneous MLF. Acetaldehyde accumulation from yeast metabolism is only temporary during wine mox. Microbes don't cause the change of residual sugar and amino acid during wine mox. Acetaldehyde accumulation from different yeast are different during wine mox.